2011
DOI: 10.1016/j.pedneo.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma Presenting With Pure Word Deafness: Report of One Case and Review of Literature

Abstract: Pure word deafness (PWD) is a rare disorder characterized by impaired verbal comprehension sparing discrimination and recognition of nonverbal sounds with relatively normal spontaneous speech, writing, and reading comprehension. Etiologies of this syndrome are varied, and there are rare reports about brain tumor with PWD in children. We report a case of medulloblastoma presented with PWD in a 7-year-old girl. She visited our outpatient clinic because of English dictation performance deterioration. PWD was diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Medulloblastoma is the most common primary brain tumor in children. , The current multimodal treatment for medulloblastoma of surgical resection, posterior fossa and craniospinal irradiation, and chemotherapy has improved 5-year survival rates from 3 to >60% over the past 50 years. , Although, there has been considerable improvement in long-term survival rates, the tumor remains incurable in about a third of patients while cognitive deficits and other quality of life (QoL) measures are often impaired in long-term survivors following radiation and high-dose chemotherapy to the developing brain. The cytotoxic agent cisplatin combined with radiation has been the cornerstone of medulloblastoma treatment for over 20 years and has produced good clinical outcomes, but these highly cytotoxic treatments are far from optimal. , There is increasing evidence that high-dose cisplatin and radiation required to circumvent tumor resistance and maintain clinical efficacy can result in lasting neurocognitive defects, stunted growth, deafness, and even secondary tumors and that the dose and frequency of cisplatin treatment is often limited by nephrotoxicity and ototoxicity. , Therefore, there is a critical need to understand the molecular pathways in medulloblastoma to identify new molecular targets that may lead to strategies to chemosensitize the tumor to safely allow dose reductions of cisplatin while maintaining clinical efficacy and resulting in improved survival and QoL outcomes.…”
mentioning
confidence: 99%
“…Medulloblastoma is the most common primary brain tumor in children. , The current multimodal treatment for medulloblastoma of surgical resection, posterior fossa and craniospinal irradiation, and chemotherapy has improved 5-year survival rates from 3 to >60% over the past 50 years. , Although, there has been considerable improvement in long-term survival rates, the tumor remains incurable in about a third of patients while cognitive deficits and other quality of life (QoL) measures are often impaired in long-term survivors following radiation and high-dose chemotherapy to the developing brain. The cytotoxic agent cisplatin combined with radiation has been the cornerstone of medulloblastoma treatment for over 20 years and has produced good clinical outcomes, but these highly cytotoxic treatments are far from optimal. , There is increasing evidence that high-dose cisplatin and radiation required to circumvent tumor resistance and maintain clinical efficacy can result in lasting neurocognitive defects, stunted growth, deafness, and even secondary tumors and that the dose and frequency of cisplatin treatment is often limited by nephrotoxicity and ototoxicity. , Therefore, there is a critical need to understand the molecular pathways in medulloblastoma to identify new molecular targets that may lead to strategies to chemosensitize the tumor to safely allow dose reductions of cisplatin while maintaining clinical efficacy and resulting in improved survival and QoL outcomes.…”
mentioning
confidence: 99%
“…Following the application of chosen criteria, we found only 21 cases of medulloblastoma associated with auditory dysfunction 5,7,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). In this study, a gender predominance for male was found (52.3% males, 47.6% females); 38% of the patients were children and 62% of the patients were adults, with a mean age of 23 years (between 2 and 50 years).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the onset of the medulloblastoma, 3 patients (14%) had the first symptoms tinnitus and sensorineural hearing loss 16,23,24 . Some patients associated other less frequent manifestations such as seizures (10% of patients), ageusia (10% of patients), progressive cranial nerve deficits, facial paralysis, swallowing difficulty, absent corneal reflex, visual impairment, quadriparesis, cognitive impairment, paretic foot musculature (in a patient with leptomeningeal spread).…”
Section: Resultsmentioning
confidence: 99%
“…Chou et al [2] hypothesized that signal changes in the bilateral temporal areas secondary to pressure effect of obstructive hydrocephalus caused pure word deafness in a paediatric patient with an infratentorial medulloblastoma. Remarkably, this patient had also complained of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Pure word deafness has been commonly reported following unilateral (dominant) or bilateral ischaemia in the temporal lobes [1]. Only a handful of cases involving pure word deafness attributable to infratentorial neoplastic lesions has been described [2,4,5,3]. …”
Section: Introductionmentioning
confidence: 99%